Earthquakes in the Netherlands cannot shake the European natural gas market - Franziska Holz; Hanna Brauers; Thorsten Roobeek (DIW Economic Bulletin, 2015)
The rising number of earthquakes in the northeastern part of the Netherlands has been attributed to the extraction of natural gas from the Groningen field. This has led tostrong opposition to natural gas production from the Dutch population, a matter that is increasingly preoccupying not only policy-makers on the local and provincial levels,but also the central government. In response, the Dutch government has decided a drastic reduction of production from the Groningen gas field, the largest natural gas field in the country. This has an impact on several Western European countries that import natural gas from the Netherlands. Model calculations by DIW Berlin based on a substantially reduced production of natural gas in the Netherlands show that due to diversified imports effects on the European natural gas market would only be small. Even if the lower Dutch production comes in addition to the disruption of the Russian supplies to Europe, it would not result in serious supply shortages or price increases in Western Europe since gas from other regions are possible. However, these supplies of natural gas would come partly from providers whose reliability might be called into question due to an unstable political situation, as for instance in North Africa.
Keywords: C69; L71; Q34; 330; natural gas; supply security